Amiodarone Induced Interstitial Lung Disease: An Enigma - Aryal, Prakash; Pantha, Srijan; Gurung, Kum Bahadur; Uprety, Augraj; Shah, Nensi; Timsina, Anup; Mandal, Dipesh; Yadav, Krishna Chandra; Adhikari, Aarati; Shahi, Rejina; et al. (Nepalese Respiratory Journal, 2024)
Amiodarone is an anti-arrhythmic drug that has potential to cause Interstitial Lung Disease (ILD) commonly non-specific Interistitial pneumonia. We present a 75-year male presenting with gradual onset progressive shortness of breath and dry cough after undergoing coronary artery bypass grafting (CABG) and was kept on amiodarone therapy post-surgery to control arrhythmias. The patient was diagnosed as amiodarone induced Non-Specific Interstitial Pneumonia (NSIP) after excluding alternative diagnosis. Early recognition and stoppage of amiodarone, prompt treatment with corticosteroid and respiratory support had favorable clinical outcome in this case.